PENGARUH PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PEMAHAMAN KONSEP IPA DAN KEMAMPUAN BERPIKIR KREATIF PADA PESERTA DIDIK SMP NEGERI 2 BULUKUMBA - Suharna Amir (OMEGA : JURNAL ILMU PENDIDIKAN DAN SAINS FISIKA, 2023)
The study aims to discover the influence of Problem Based Learning on science conceptual understanding and creative thinking skills of grade VIII students at SMPN 2 Bulukumba. Based on the results of descriptive analysis and inferential analysis on the test of students; conceptual understanding and creative thinking skills taught by using Problem Based Learning in the experimental class and the the ones taught by using conventional learning in the control class, the results obtained are: 1) the students’ conceptual understanding in the experimental class obtained maximum and minimum scores of 96 and 68, 2) the students’ conceptual understanding in the control class obtained maximum and minimum scores of 84 and 56, 3) the students’ creative thinking skills in the experimental class obtained maximum and minimum scores of 92 and 48, 4) the students’ creative thinking skills in the control class obtained maximum and minimum scores of 84 and 26, 5) the science conceptual understanding in the experimental class is better than the control class with each value of the experimental class is 79.17 from a maximum value of 100 with a standard deviation of 8.03, and the control class average is 67.6 from a maximum value of 100 with a standard deviation of 7.71, although the range of values ​​obtained by students is still in moderate - good category, and 6) the creative thinking skills in the experimental class is better than the control class with the average value of the control class is 72.97 of the maximum value is 100 with a standard deviation of 11.74, and the control class average is 50 from the maximum value of 100 with a standard deviation of 16.09, even though the range of values ​​obtained by students is still in poor - good category.